Recycling spent bleaching earth and oil palm ash to tile production: Impact on properties, utilization, and microstructure - Srisang, Siriwan; Srisang, Naruebodee (My University, 2021)
Spent bleaching earth (SBE) and oil palm ash (PA) were recycled to utilize as substitute material for producing tile. The proper quantity of SBE and PA in three clay groups (40, 60, and 80% by weight) was explored combined with varying compression pressure (90, 100 and 110 bar) and firing temperature (1000 and 1100 °C). All conditions were analyzed the influence and interaction of producing factors, i.e. mixture (M), compression pressure (C), and firing temperature (F) on tile attributes. Tile utilizations (water absorption, strength, acid resistance, color and leaching heavy metal) and cost were compared with the commercial tile. The microstructures were also examined. Results found that the mixture B at high clay group provided low water absorption ≈ 5–6%, moderate TBL ≈620–630 N, low corrosion ≈0.015–0.026%, and there were cheaper cost and better utilizations than commercial tile. Mixture B detected enough quartz and mullite which provided more strength. Hence, the SBE and OPA can be utilized for tile production with the tile properties agreed with industrial standard.
Keywords: Microstructure; Oil palm ash; Spent bleaching earth; Tile; Tile properties; Tile utilizations